Deficits in Psycho-Oncological Care among Turkish Immigrant Women with Breast Cancer in Germany – An Interview Study. - Spallek Lena; Yılmaz-Aslan Yüce; Klein-Ellinghaus Funda; Gök Yeşim; Zeeb Hajo; Kolip Petra; Spallek Jacob (International Journal of Psychotherapy Practice and Research, 2017)
Objective: Aim of this study was to assess appraisal and utilization of psycho-oncological care of Turkish female breast cancer patients in Germany. The presented results are part of a larger study about care of female German and Turkish cancer patients in Germany (4B-study). Methods: In this qualitative study semi-structured face to face interviews were conducted with Turkish breast cancer patients in Germany. Interviews were transcribed and analyzed in Turkish by two Turkish speaking researchers via content analysis using MAXQDA qualitative analysis software (version 11). Results were discussed among a bilingual research team. Selected citations were translated. Results: Turkish patients showed a great need for support, particularly emotional and informational support. However, the available psycho-oncological care was rarely used due to lack of information, prejudice, language and cultural barriers. A missing belief in effectiveness of psycho-oncological care was also noted. Conclusions: According to this study, psycho-oncological services do not adequately correspond to the needs of Turkish breast cancer patients. If confirmed in more extensive studies, these findings call for the development of migrant-sensitive approaches and therapeutic action to provide ease to cancer patients. Additionally, prejudice against psycho-oncological care needs to be reduced in the Turkish community.
Keywords: breast cancer